Penggunaan minyak goreng bekas dan minyak segar dalam pakan ayam petelur terhadap kualitas fisik dan kolesterol telur=The Effect of Used and Fresh Cooking Oil in the Layer Diets on Fisical Quality and Cholesterol ... - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2005)
The research were aimed to evaluate the effect of used cooking oil (UCO) and fresh cooking oil (FCO) in the layer diets on fisical quality and cholesterol content of egg. One hundreds and fifty of 20 weeks old layers were randomly devided into five treatments with three replications of 10 layers each. The treatments were Rg (control feed without UCO and FCO), R, (feed with 3% UCO), Rj (feed with 5% UCO), R3 (feed with 3% FCO) and R4 (feed with 5% FCO). The data were analyzed by analyses of variance and orthogonal contrast test. The results indicated that egg weight, shell thickness, shell weight and HU had no significant differences between treatments, and had significant differences (P < 0,01) on yolk colour. The cholesterol had significant differences (P < 0,01) on 40 weeks old, and had no significant differences on egg fat.